INTERSECTORAL PARTNERSHIP AS A FACTOR IN THE DEVELOPMENT OF AN ECOLOGICALLY ORIENTED ECONOMY - Vakhtina, M.A (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2020)
The extensive development of the Russian economy, focused only on economic growth, in recent years has led to serious violations of the ecological balance, an increase in the cost of restoring damage to the environment and humans. An objective need arose to form a mechanism for an environmentally oriented economy. Participants in this mechanism should be not only government agencies, but also the business community and public organizations. So far, interaction between sectors in achieving sustainable development goals in Russia has not been properly established. Business lacks motivation to introduce the best environmentally friendly technologies, civil society remains weak and controlled by the state. It is necessary to strictly follow the requirements developed by the international community for the implementation of the concept of sustainable development based on the integration of the economy, ecology and social sphere.